Production of Benzyl Isothiocyanate from Moringa peregrina (Forssk.) Fiori via Suspension Cultures - Mustafa, Sabha Selmy; Gabr, Mahdia Farid; Hegazi, Ghada Abd El-Moneim (Plant Tissue Culture and Biotechnology, 2023)
Benzyl isothiocyanate (BITC) is one of the main constituents of Moringa peregrina, an endangered species in the flora of Egypt. The purpose of this study was to establish a procedure to enhance the in vitro production of BITC in Moringa peregrina suspension cultures. This could then aid in the mass production of this useful pure active compound and avoid the exploitation of natural resources of this valuable plant. Suspension cultures of Moringa peregrina was established from callus cells in liquid MS medium supplemented with 10.74 μM naphthalene acetic acid, 2.325 μM kinetin, in addition to salicylic acid as an elicitor and/or L-phenylalanine as a precursor of BITC. The combination of both salicylic acid and L-phenylalanine gave the highest accumulation of BITC after two weeks with 10.42-fold increase, compared to its content in the mother plant. This study is promising for the large-scale production of BITC, which has been identified as an anticancer agent with possible applications in the pharmaceutical industry. Plant Tissue Cult. & Biotech. 33(2): 85-95, 2023 (December)